Long noncoding RNA MIR31HG and its splice variants regulate proliferation and migration: prognostic implications for muscle invasive bladder cancer - Wu, Sheng; Nitschke, Katja; Worst, Thomas; Fierek, Alexander; Weis, Cleo-Aron Thias; Eckstein, Markus; Porubský, Štefan; Kriegmair, Maximilian; Erben, Philipp (Journal of experimental & clinical cancer research, 2020)
Growing evidence supports the pivotal role of long non-coding RNAs (lncRNAs) in the regulation of cancer development and progression. Their expression patterns and biological function in muscle invasive bladder cancer (MIBC) remain elusive.